Gender Bias in Islamic Children’s Literature: Case Study in Indonesia - Radius Setiyawan; Sri Lestari (Universitas Muhammadiyah Malang, 2021)
Children's books with Islamic content are popular in Indonesia. The motivation of parents to introduce this genre of books is to help them teach their children the faith and knowledge of Islam from an early age. The more complete the information about Islam available in the book, the more parents will consider buying the book. Meanwhile, consideration of books with content that introduces gender equity needs to be considered. This study analyzes the gender bias in stories of Islamic content. The books analyzed are several popular books published by various different publishers. The research method used was qualitative and the narrative and visual data were critically analyzed with a gender perspective. Feminist linguistics was used to more deeply reveal the signs that will be described based on the context that surrounds the female character. The depiction of women in the four books is generally represented by traditional gender patterns. The female figure is depicted as dependent on men, not involved in dominant narratives. The female characters are described as weak while the male characters are described as stronger without regard to the female character.